Gonadotropin secretion and ovarian response of KISS1 knockout gilts treated with hormone analogs activating the hypothalamic–pituitary-gonadal axis - Ahern, Daniel F; Wilson, Kyle E; Wijesena, Hiruni R; Ross, Caitlin E; Elsken, Dorothy H; Flórez, Julio M [UNESP]; Martins, Kyra; Beltramo, Massimiliano; Sonstegard, Tad S; Cushman, Robert A; White, Brett R; Lents, Clay A (Oxford University Press (OUP), 2025)
Kisspeptin knockout (KISS1-/-) pigs exhibit hypogonadotropic hypogonadism. Hormone analogs targeting different levels of the hypothalamic-pituitary-gonad axis were used to characterize the secretion of reproductive hormones (LH and FSH) and ovarian responses (estradiol and progesterone) in KISS1-/- gilts. Uteri and ovaries were collected from KISS1+/+ and KISS1-/- gilts to confirm ovulatory outcomes. Pulses of LH and FSH were observed in KISS1-/- gilts that differed (P < 0.05) in amplitude and nadir from pulses in wild-type KISS1+/+ and KISS1+/- gilts. A neurokinin B (NKB) agonist stimulated LH but not FSH in wild-type gilts, whereas NKB affected neither LH nor FSH in KISS1-/- gilts. The kisspeptin receptor agonist, C6, stimulated LH secretion in wild-type gilts but not in KISS1-/- gilts (P < 0.05). Secretion of LH in KISS1-/- gilts depends on the dose and frequency of GnRH. Priming with estradiol-17β and GnRH before PMSG and hCG treatment resulted in luteal structures on the ovary of KISS1-/- gilts, though ovulation rate was less (P < 0.05) than KISS1+/+ gilts. This is the first report showing NKB regulation of LH secretion in swine. It is confirmed that a single copy of the KISS1 allele in gilts confers normal gonadotropin secretion following stimulation with NKB, kisspeptin and GnRH analogs. The sustained activation of the kisspeptin receptor by C6 generated long-lasting LH secretion in gilts to induce ovulation. Ovulation in KISS1-/- gilts is possible, but treatments need optimization to maximize ovulation rate.